119 Results through relationships: improving personalised care towards the end of life. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Dorman, Saskie; Rogers, Adrienne; Howard, Sarah; Macdonald, Fiona; Brogan, Andy
Abstract : Background: In spring 2018, NHS England invited Dorset to be a demonstrator site for improving personalised care towards the end of life. Our purpose: 'In my last year of life, help me to live well until I die'. Method: We seized the opportunity to take a different approach, understanding what people really needed, what mattered to them, and crucially, why. We developed six core capabilities and compared them with what actually happened, by bringing together services to map experiences of people and their families in detail, and observing interactions as they happened. We triangulated this with quantitative data including measures of informal support; advance care planning, investigations, treatments, admissions, length of stay, contacts with services in the last year of life, and place of death. Results: We identified previously hidden assumptions about the way the work worked, and themes started to emerge, such as a tendency for: viewing people in isolation, rather than through their relationships and context, and recording facts rather than stories; focusing on interventions, services and organisations rather than relationships and community; assessing, diagnosing and reacting to what's happened, rather than thinking and learning together, developing shared understanding and anticipating and planning ahead. Conclusions: A paradigm shift is needed in the way we think about the work and the people we support. This approach highlights implicit assumptions in the way systems currently work, and provides opportunities for shared sense-making and fundamental change. Collaborators: Dorset CCG, Poole North, Dorset End of Life Care Partnership, NHS England Facilitation, coaching: Easier, Inc. Funding: NHS England Personalised Care Group